1997
DOI: 10.1111/j.1439-037x.1997.tb00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Change of Carbohydrate Content of Two Varieties of Jerusalem Artichoke Tubers (Helianthus tuberosus L.) During Cold Storage Conditions (4°C)

Abstract: The Jerusalem artichoke (Helianthus tuberosus L.) represents an interesting source of carbohydrate because of its high fructose content (75 % of total carbohydrates). An experiment on storage of two varieties of the Jerusalem artichoke tubers ("Kharkov' and 'Violet de Rennes') showed that the quality of tubers was preserved during the first 7 weeks of cold storage. Beyond this period, the loss in total carbohydrate content was evaluated at 0.19% for the 'Kharkov' and 0.26% for the 'Violet de Rennes' variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The reduction in dry matter during the last period of storage might be attributed to the higher rate of sugar loss through respiration than the water loss through transpiration (Wills et al, 1981). Ben Chekroun et al (1997) showed that the dry matter of Jerusalem artichoke tubers maintained for the first 7 weeks of cold storage beyond this period, a decrease trend takes place until the end of the storage.…”
Section: Dry Mattermentioning
confidence: 99%
“…The reduction in dry matter during the last period of storage might be attributed to the higher rate of sugar loss through respiration than the water loss through transpiration (Wills et al, 1981). Ben Chekroun et al (1997) showed that the dry matter of Jerusalem artichoke tubers maintained for the first 7 weeks of cold storage beyond this period, a decrease trend takes place until the end of the storage.…”
Section: Dry Mattermentioning
confidence: 99%
“…Most of carbohydrates consist of water-soluble inulin. Concentration of inulin reaches 50 -56% of dry matter or 11.3 -14.2 g 100 g'' of fresh mass of tubers (Ben-Chekroun et al, 1997).…”
Section: Introductionmentioning
confidence: 97%